La direction d’école primaire, une question de pouvoir ? - Cécile Roaux (Recherches en Éducation)
This article proposes to examine how the transformation of the educational "repository" weakens the position of school principals in France and raises the question of their power. If the responsibilities of the latter have increased, approaching those of the heads of secondary schools, the primary school remains marked by a division of educational work and a patriotism of corps to preserve the autonomy of the actors in the class. Based on a survey by questionnaire raising the question of the status of school principals, the ideological break between teachers and principals will be studied, which has the effect of assigning the latter to devalued work, placing them on the fringes of the functioning of the school for which they are nevertheless solely responsible. Our analytical framework is that of the sociology of organizations and systems.